2017
DOI: 10.1186/s13018-017-0681-1
|View full text |Cite
|
Sign up to set email alerts
|

Selective medial soft tissue release combined with tibial reduction osteotomy in total knee arthroplasty

Abstract: BackgroundTo obtain the correct coronal alignment and balancing in flexion and extension, we established a selective medial release technique and investigated the effectiveness and safety of the technique during primary total knee arthroplasty (TKA).MethodsFour hundred sixty-six primary TKAs with varus deformity were prospectively evaluated between June 2013 and June 2015. A knee joint position similar to Patrick’s sign was used to release the medial structure. The medial release technique consisted of release… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…However, this may have negative impact on long-term durability for the TKA. 2,4 With these limitations to the medial release, the medial epicondylar osteotomy seems to be a good alternative for knee balance in TKA. Our results confirmed that epicondylar osteotomy in one knee resulted in outcomes similar to those of the contralateral side with a good medial release.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this may have negative impact on long-term durability for the TKA. 2,4 With these limitations to the medial release, the medial epicondylar osteotomy seems to be a good alternative for knee balance in TKA. Our results confirmed that epicondylar osteotomy in one knee resulted in outcomes similar to those of the contralateral side with a good medial release.…”
Section: Discussionmentioning
confidence: 99%
“…Due to preoperative deformity, some ligaments around the knee are contracted that will be carefully released in a stepwise manner to balance the soft tissues around the knee and allow optimum knee kinematics. Several structures may be addressed during correction of severe varus deformity: (1) removal of osteophytes, (2) increase in the pes anserine complex release, (3) release of the tibial insertion of the deep head of the medial collateral ligament (MCL), (4) posteromedial capsule complex, (5) resection of the posterior cruciate ligament (PCL), and (6) release of the superficial MCL medially and posteriorly. [1][2][3] In varus knees, most surgeons prefer to release or elevate the soft tissues of the tibial insertion site by either sharp or blunt techniques.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As described by Tang et al [8], we fully flexed the knee to subluxate the joint forward and outward using a Hoffman hook. The tibial plateau and posteromedial corner structures were completely exposed, and subperiosteal release was performed as that in experimental group.…”
Section: Step 2 In Control Group (Conventional Full Flexion)mentioning
confidence: 99%
“…However, a cadaver study 15 considered the success of the MCL pie-crusting technique is likely technique dependent since failure occurs within the ligament itself. A new-published article 16 also found that the pie-crusting technique has a higher rate of failure in the ML gap balance compared with reduction osteotomy.…”
Section: Introductionmentioning
confidence: 98%